ANALISIS KEPUASAN WISATAWAN TERHADAP KUALITAS PRODUK WISATA KULINER SATE IKAN TANJUNG DI KABUPATEN LOMBOK UTARA - Ni Putu Hendri Widiartini; Lalu Yulendra; Muhammad Azizurrohman (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine tourist satisfaction with the quality of Tanjung Fish Satay tourism products in Lombok Regency. This study is a quantitative descriptive study with four sub-variables of tourist satisfaction expectations, performance, comparison, confirmation/disconfirmation as independent variables and one tourism product quality as the dependent variable. The population in this research are tourists who buy tanjung fish satay tourism products and the sample used is 50 respondents and the sampling technique uses porposive sampling with a specific goal, namely tourists who buy cape fish satay products at least twice. Data collection techniques using questionnaires, documentation, interviews, and observations. The data analysis technique used is multiple linear regression with the help of SPSS application. The results of this study indicate that the sub-variables of expectation, performance, comparison, confirmation/disconfirmation partially have a significant effect on the quality of tourism products. The results of the t-test (partial) also show that the sub-variable expectations, comparisons have no significant effect on tourism products and expectations and the actual performance of the product have a significant effect on product quality. Based on the results of the F (simultaneous) test, it shows that the sub-variables of tourist satisfaction expectations, performance, comparison, confirmation/disconfirmation simultaneously have a significant effect on tourism products.